Comparison the nutrients in soybean products between primary analysis and NIR analysis - Maskhairiah, Ismail (2010)
The objective on this research is to determine the nutrients contents in soybean products using 2 method analysis which are primary analysis and NIR analysis.The scope of study are focus on small scale production of soybean products.Small scale industry normally lack of good production because of the less technologies and experiences.Therefore,there is no specific data about nutrient contents in soybean foods that attached to the food packaging The primary analysis are bases on the conventional method;Kjedahl’s method to determine the protein contents,Soxhlet’s method to determine the fat contents,fiber method to determined the fiber contents and ash method to determine the ash content in soybean products.By using NIR,it cans analysis and determines the pattern of nutrient content in soybean products and compares the nutrient contents between NIR analysis and primary method analysis.From the experiment, the results between primary analysis and NIR analysis have small error and it almost similar as it discuss in chapter 4.Most of the nutrients contents; protein,fat,fiber and ash have small errors.NIR is a clone from primary analysis since all the data was determined from primary methods;Kjedahl Method,Soxhlet Method,Fiber Method and Ash Method.NIR is an instrument that will help to determined nutrients contents in faster route but somehow it is not too accurate since NIR consider with size,shape and distribution of particles of samples.The primary analysis is the best method to determine the nutrients contents since it more accurate compare than NIR analysis